The use of adaptation training in the immediate postoperative period in patients with acquired defects of the maxillofacial region - E. V. Kochurova; E. O. Kudasova; V. N. Nikolenko; D. V. Uklonskaya; O. I. Panferova (Опухоли головы и шеи, 2022)
Introduction. Surgical treatment of tumors in the maxillofacial region is always accompanied by the involvement of a significant amount of bone structures of the jaws. At the same time, the main method of dental orthopedic treatment of patients is prosthetics with a removable prosthesis. The larger the defect in the maxillofacial region, the more pronounced the subjective feeling of the patient’s rejection of the removable structure.There is a close relationship between the adaptive ability of a person and oral stereognosy as the anatomical and physiological mobility of the tongue and the synthetic activity of the cerebral cortex.One of the options for improving adaptability and increasing the activity of the synthetic activity of the cerebral cortex is a special adaptation training, which includes articulatory movements of the tongue. Stimulation of the muscles of the cheeks and lips with the tongue contributes not only to normal pronunciation / improvement of the intelligibility of the speech stream, but also adapts the tongue to the changed conditions after the imposition of removable prostheses.In connection with the above data, the study objective is to analyze the effectiveness of adaptive training to improve adaptability to removable dentures in patients with acquired defects of the maxillofacial region.Materials and methods. Dental orthopedic treatment of 39 patients was carried out after surgical treatment, including resection of the upper jaw and simultaneous replacement with a removable dental resection shaping prosthesis of the upper jaw directly on the operating table.A clinical control group (n = 40) was introduced to identify parameters in determining the synthetic activity of the cerebral cortex. Depending on the assigned adaptive support, the patients were divided into 2 subgroups: Subgroup 1 – the modernized adaptation training complex was prescribed (n = 18), Subgroup 2 – the standard observation of the patient (n = 21).Stereognostic testing and determination of adaptive capacity before treatment, after 7 / 14 days and 1 / 3 month after the placement of a resection prosthesis.Results. Adaptive support for patients of Subgroup 1 is represented by adaptation training 1 complex (33.3 %). Repeated stereognostic testing 7 days after surgery showed a decrease in adaptive values in all patients. After 14 days, in Subgroup 2, stereognostic testing of patients remained unchanged. Another 14 days (1 month after the placement of a resection prosthesis) in the Subgroup 1 of patients, the reference test values were found in 2.5 % of cases. The number of patients with high and moderate values increased by 1.3 times, and the number of patients with low test values also decreased by 3 times. 3 months after the placement of the resection prosthesis, the test values in Subgroup 1 approached the values before the surgical treatment. None of the patients of Subgroup I had a low level of adaptability.Discussion. The training exercises contributed not only to the muscular development of the tongue, but also stimulated the synthetic activity of the cerebral cortex. In 3 months after the placement of a resection prosthesis in the 1st subgroup of patients, the values of stereognostic testing approached the preoperative level.Conclusion. Normalization of the tone of the muscles of the oral cavity through functional training changes the stereognostic abilities of the patient. All this together increases the patient»s adaptability to removable dentures. Adaptation support reduced the time of adaptation to new removable dentures, which was confirmed by objective research – stereognostic testing. The influence on the synthetic activity of the cerebral cortex through the exercises of training for the tongue increased the adaptability to the resection prosthesis, changed the quality of life for the better.